Eco-Label Adoption and Sustainable Consumption in the Batik Industry: A SWOT-Based Consumer Assessment in Jakarta, Indonesia - I Wayan Koko Suryawan (Journal of Sustainable Infrastructure, 2026)
The growing demand for environmentally responsible products presents new opportunities for the Indonesian batik industry to strengthen its competitiveness while supporting sustainable development objectives. Eco-labeling has emerged as a potential instrument for communicating environmental performance and promoting sustainable consumption; however, consumer acceptance of eco-labeled batik remains poorly understood. This study examines the strengths, weaknesses, opportunities, and threats (SWOT) associated with the adoption of eco-labels in the batik industry from the perspective of consumers in Jakarta. The analysis explores how environmental awareness, cultural identity, purchasing behavior, and sustainability concerns influence consumer perceptions toward eco-labeled batik products. The findings indicate that eco-labels can enhance consumer trust, product differentiation, and market appeal, particularly among younger consumers who are increasingly concerned about environmental and social issues. However, challenges remain regarding consumer understanding of eco-labels, higher product prices, limited information transparency, and the risk of greenwashing. Opportunities are supported by increasing sustainability awareness, government initiatives promoting environmentally friendly batik production, and the growing influence of digital marketing channels. Meanwhile, competition from fast fashion products, limited standardization of eco-label certification, and economic uncertainty pose significant threats. The study suggests that integrating eco-label certification, sustainability communication, and digital traceability mechanisms can strengthen consumer confidence and increase market acceptance of environmentally responsible batik products. These findings provide practical insights for policymakers, industry stakeholders, and batik producers seeking to promote sustainable consumption and enhance the long-term competitiveness of Indonesia’s batik industry.